2021
DOI: 10.1097/dcr.0000000000002122
|View full text |Cite
|
Sign up to set email alerts
|

Organ Preservation in Patients with Rectal Cancer Treated with Total Neoadjuvant Therapy

Abstract: BACKGROUND: Retrospective studies suggest that watch-and-wait is a safe alternative to total mesorectal excision in selected patients with a clinical complete response after chemoradiotherapy. OBJECTIVE: This study aimed to determine the proportion of patients with rectal cancer who may benefit from watch-and-wait. DESIGN: This study is a retrospective analysis of data from prospectively maintained databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“… 22 Studies have used deep learning to examine prognosis, identify prognostic biomarkers, and in predicting molecular profiles, based on standard H&E-stained slides in CRC. 23 , 24 , 25 , 26 As new treatment strategies with total neoadjuvant treatment and immunotherapy emerge, 27 , 28 , 29 an accurate tumor regression grade is highly important as the pathological response often is used as endpoint in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Studies have used deep learning to examine prognosis, identify prognostic biomarkers, and in predicting molecular profiles, based on standard H&E-stained slides in CRC. 23 , 24 , 25 , 26 As new treatment strategies with total neoadjuvant treatment and immunotherapy emerge, 27 , 28 , 29 an accurate tumor regression grade is highly important as the pathological response often is used as endpoint in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was also observed in data reported from the IWWD [54]; in patients with local regrowth, the incidence of distant metastasis was 18%, while in those without it was 5%. Jimenez-Rodriguez et al also found a high rate of distant metastases (~50%) in the small number of patients (6%) treated with TNT by a single surgeon that actively performed WW [59] who experienced local regrowth.…”
Section: Oncologic Outcomesmentioning
confidence: 93%
“…Jimenez-Rodrigues et al [ 164 ] analyzed 88 patients with stage II and III rectal cancer who received an induction-type total neoadjuvant therapy (TNT) consisting of 8 cycles of FOLFOX or XELOX before chemoradiotherapy between 2012 and 2019. They reported that TNT using induction chemotherapy followed by chemoradiotherapy could achieve a cCR in 36.2% of patients, and watch-and-wait protocol could be advised.…”
Section: Debated Issuesmentioning
confidence: 99%
“…As colorectal surgeons, we have experienced patients who show a cCR after NCRT. Furthermore, the adoption of induction or consolidation chemotherapy in total neoadjuvant treatments [ 164 ] has increased the incidence of cCR. The watch-and-wait strategy also got more attention because salvage surgery for regrowing tumors during follow-up did not compromise an oncologic outcome.…”
Section: Debated Issuesmentioning
confidence: 99%